Re-Designing Independent Campus Model in Islamic Boarding School Higher Education - Fawaid, Achmad; Abdullah, Abdullah; Huda, Miftahul (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This research has the purpose to (1) test the effectiveness of the MBKM program model at Nurul Jadid University through limited trials; (2) conduct an evaluation and revision of the model; (3) carry out a broader model trial for the development of future MBKM prototype programs. This research employs a Research and Development approach with two implementation phases. The research outcomes indicate that in the first phase, an exploratory research and prototype design of the MBKM program were conducted through the MBKM Santri Mengabdi and MBKM Santri Mengajar programs. In the second phase, a trial of the MBKM program design was conducted with a limited group, and the outcomes demonstrated the success of the MBKM Santri Mengabdi and MBKM Santri Mengajar programs, serving as prototypes for the independent development of MBKM by Nurul Jadid University. Through evaluation and revisions, it was found that the MBKM Santri Mengabdi and MBKM Santri Mengajar programs are suitable for broader implementation, even though some technical adjustments were identified. The outcomes of the program trial indicate that the MBKM Santri Mengabdi and MBKM Santri Mengajar programs are suitable for implementation and are proposed to be carried out in all research programs at Nurul Jadid University in Paiton, Probolinggo.